Young adult experiences with securing employment: Perceptions of and experiences with employer discrimination and expectations hinder successful labour market attachment - Shier, Micheal L.; Graham, John R.; Goitom, Mary; Eisenstat, Marilyn (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2014)
The increasingly precarious nature of North America’s labour market has created challenges for young adults in securing and maintaining adequate employment. In a study to better understand these barriers one to one interviews and focus groups were conducted with 36 young adults (between ages 18 and 29) in one neighborhood in Toronto, Canada. Findings show that varying forms of discrimination experienced and perceived by respondents when searching out employment, along with expectations of employers within current labour markets, act as key barriers impacting successful labour market attachment. The findings suggest that these challenges experienced by young people in the labour market can have a lasting psychosocial impact on young people when attaching to the labour market. There is a present need to address both negative socio-cultural perceptions of young adults (and those held by young adults) and the precarious aspects of the labour market that support and maintain social inequality through more substantive policy, regulatory and program based initiatives.